Structure- and adatom-enriched essential properties of graphene nanoribbons - Lin, Shih-Yang (Boca Raton : CRC Press, Taylor & Francis Group, 2018)
Structure- and Adatom-Enriched Essential Properties of Graphene Nanoribbons offers a systematic review of the feature-rich essential properties in emergent graphene nanoribbons, covering mainstream theoretical and experimental research. It includes a wide range of 1D systems; namely, armchair and zigzag graphene nanoribbons with and without hydrogen terminations, curved and zipped graphene nanoribbons, folded graphene nanoribbons, carbon nanoscrolls, bilayer graphene nanoribbons, edge-decorated graphene nanoribbons, and alkali-, halogen-, Al-, Ti, and Bi-absorbed graphene nanoribbons. Both multiorbital chemical bondings and spin arrangements, which are responsible for the diverse phenomena, are explored in detail. First-principles calculations are developed to thoroughly describe the physical, chemical, and material phenomena and concise images explain the fundamental properties. This book examines in detail the application and theory of graphene nanoribbons, offering a new perspective on up-to-date mainstream theoretical and experimental research.
OCLC-licensed vendor bibliographic record.
Keywords: Nanostructured materials; Graphene; SCIENCE / Solid State Physics; TECHNOLOGY / Material Science